A selective C5a-derived peptidomimetic enhances IgG response following inactivated SARS-CoV-2 immunization and confers rapid disease resolution following murine coronavirus infection - Neville, Andrew J.; Conrin, Mackenzie E.; Schulze, Thomas T.; Davis, Paul H. (Frontiers in Immunology, 2025)
The host complement system is a critical component of innate immunity and serves as a principal mechanism of pathogen defense in mammals. EP67 is an engineered decapeptide derived from the C terminus of human complement protein C5a, which displays selective immunostimulatory activity. EP67 preferentially activates phagocyte mononuclear cells but shows minimal activity towards inflammatory granulocytes, including neutrophils. Previous studies of viral infection showed that EP67 possessed antiviral efficacy when used following infection and enhanced antibody responses to antigen challenges when used as an adjuvant. Here, we show in a rodent model that immunization with inactivated γ-irradiated SARS-CoV-2 in combination with EP67 can produce elevated nucleocapsid-specific IgG antibodies compared to viral lysate alone, supporting an enhanced adaptive immune response. Additionally, intranasal administration of EP67 following infection with live MHV-A59 coronavirus resulted in a rapid health improvement in symptomatic infections compared to PBS vehicle controls. Taken together, these results suggest EP67 shows efficacy towards betacoronaviruses when used as an adjuvant during immunization or as a therapeutic during active infections. Moreover, these findings continue to support the capability of EP67 as an antiviral agent and a useful immunostimulatory peptide.